Kamus kawi - Jawa menurut kawi-Javaansch woordenboek / C.F. Winter Sr dan R. Ng Ranggawarsita; alih aksara, Asia Padmopuspito dan A. Sarman Am, I. Supriyanto - WINTER Sr, C.F.; Ranggawarsita, Raden Ngabehi, 1802-1874; Supriyanto, I.; Sarman Am, A.; Asia Padmopuspito (Gadjah Mada University Press, 1990)
x, 311 hlm. ; 22 cm.